Growth and Characterization of Titanium Dioxide Nanorods Via Hydrothermal Method - Munawwer, Athirah; Ameruddin, Amira Saryati (Enhanced Knowledge in Sciences and Technology, 2023)
Extensive study has been carried out for wide band gap semiconductor materials such as titanium dioxide (TiO₂) due to their potential application in photovoltaics and sensors. In particular, TiO₂ nanostructures are of interest due to the larger surface area and the ability for bandgap tunability. In this study, titanium dioxide (TiO₂) nanorods were fabricated using the hydrothermal method on fluorine doped tin oxide (FTO) with different variation growth solution parameters at a constant reaction time of 7 hours. The parameter variation in this study were reaction temperature, concentrations of hydrochloric (HCL) acid solution and concentrations of titanium (IV) butoxide (TBOT) solution. The structural analysis of the samples was characterized by using X-ray Diffraction (XRD) while the composition of the sample was obtained by the Energy Dispersive X-Ray (EDX) analysis. The surface morphology of the samples was characterized by Field Emission Scanning Electron Microscopy (FESEM) and Ultraviolet–Visible Spectrophotometer (UV – Vis) were used to characterize the optical properties of the samples. The structural analysis had proven that the TiO₂ nanorods consist of pure rutile phased. The composition analysis showed that TiO₂ compounds had been fabricated on the substrates. From the surface morphology and optical properties analysis, the best sample was found to be fabricated at a reaction temperature of 150 ℃ with the precursor solution of 30 ml of HCl acid solution and deionized (DI) water with a volume of ratio was 1:1 and the volume of TBOT at 1.5 ml for 7 hours.